Grading Central Diabetes Insipidus Induced by Immune Checkpoint Inhibitors: A Challenging Task - Barnabei, Agnese; Strigari, Lidia; Corsello, Andrea; Paragliola, Rosa Maria; Iannantuono, Giovanni Maria; Salvatori, Roberto; Corsello, Salvatore Maria; Torino, Francesco (Frontiers in Endocrinology, 2022)
Central diabetes insipidus (CDI) is a rare endocrine disease deriving from an insufficient production or secretion of anti-diuretic hormone. Recently, CDI has been reported as a rare side effect triggered by immune checkpoint inhibitors (ICI) in cancer patients. Despite its current rarity, CDI triggered by ICI is expected to affect an increasing number of patients because of the expanding use of these effective drugs in a growing number of solid and hematologic malignancies. An appropriate assessment of the severity of adverse events induced by anticancer agents is crucial in their management, including dosing adjustment and temporary withdrawal or discontinuation treatment. However, assessment of the severity of CDI induced by ICI may be challenging, as its main signs and symptoms (polyuria, dehydration, weight loss, and hypernatremia) can be incompletely graded. Indeed, the current grading system of toxicity induced by anticancer treatments does not include polyuria. Additionally, dehydration in patients affected by diabetes insipidus, including ICI-induced CDI, is different in certain aspects from that due to other conditions seen in cancer patients, such as vomiting and diarrhea. This prompted us to reflect on the need to grade polyuria, and how to grade it, and to consider a specific grading system for dehydration associated with CDI induced by ICI. Here we propose a new grading system for polyuria and dehydration, as critical symptoms of the CDI syndrome occurring in patients on ICI treatment, to obtain better management of both the adverse event and the triggering drugs.